Identification of Minimal p53 Promoter Region Regulated by MALAT1 in Human Lung Adenocarcinoma Cells - Tano, Keiko; Onoguchi-Mizutani, Rena; Yeasmin, Fouzia; Uchiumi, Fumiaki; Suzuki, Yutaka; Yada, Tetsushi; Akimitsu, Nobuyoshi (Frontiers in Genetics, 2018)
The MALAT1 long noncoding RNA is strongly linked to cancer progression. Here we report a MALAT1 function in repressing the promoter of p53 (TP53) tumor suppressor gene. p21 and FAS, well-known p53 targets, were upregulated by MALAT1 knockdown in A549 human lung adenocarcinoma cells. We found that these upregulations were mediated by transcriptional activation of p53 through MALAT1 depletion. In addition, we identified a minimal MALAT1-responsive region in the P1 promoter of p53 gene. Flow cytometry analysis revealed that MALAT1-depleted cells exhibited G1 cell cycle arrest. These results suggest that MALAT1 affects the expression of p53 target genes through repressing p53 promoter activity, leading to influence the cell cycle progression.